Pengaruh Joyfull Learning terhadap Motivasi Belajar di SDN Karah I Surabaya - PRINOTAMA, ALBERTA NOVARA; LARASATI, DIYAS AGE; ROOSYANTI, ANNA (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2019)
The purpose of this study was to determine the effect of Joyfull Learning methods on student motivation in social studies subjects at SDN Karah I Surabaya. This type of research used quasi-experimental (Quasi Experiment), the research approach is quantitative. The population research was 5th Grade Student of SDN Karah I Surabaya in academic year 2018/2019. The sample in this study were students of class V-A and V-B, amounting to 40 students in each class, researchers used this sample because from previous observations class V-A and V-B were still lacking motivation in learning. Based on the results of the analysis show that there is an influence of the level of motivation of students learning in class V by using the Joyfull Learning method, it can be seen that the significance value is 0,000 <0.05, so there is an influence of Joy Learning learning on learning motivation in social studies material class V SDN Karah I Surabaya.